2011
DOI: 10.1071/fp11124
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the domestication of common bean (Phaseolus vulgaris) using multilocus sequence data

Abstract: Abstract. Multilocus sequence data collected from domesticated and related wild relatives provides a rich source of information on the effect of human selection on the diversity and adaptability of a species to complex environments. To evaluate the domestication history of common bean (Phaseolus vulgaris L.), multilocus sequence data from landraces representing the various races within the Middle American (MA) and Andean gene pools was evaluated. Across 13 loci, nucleotide diversity was similar between landrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
3
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 112 publications
2
75
3
4
Order By: Relevance
“…Multiple domestication processes have been reported for the Phaseolus genus (Gepts and Debouck, 1991), and the domestication of common bean (Phaseolus vulgaris) occurred independently in different gene pools approximately 8000 years ago (Mamidi et al, 2011;Serrano-Serrano et al, 2012). According to the Food and Agriculture Organization (FAO, 2012), dry bean is grown in 126 countries, and the estimated global production of this legume was 25 million tons in 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple domestication processes have been reported for the Phaseolus genus (Gepts and Debouck, 1991), and the domestication of common bean (Phaseolus vulgaris) occurred independently in different gene pools approximately 8000 years ago (Mamidi et al, 2011;Serrano-Serrano et al, 2012). According to the Food and Agriculture Organization (FAO, 2012), dry bean is grown in 126 countries, and the estimated global production of this legume was 25 million tons in 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Within the Mesoamerican gene pool, random amplified polymorphic DNA (59) and chloroplast data (60) have been interpreted as indicating independent domestication events. However, using coalescent simulation and ABC, Mamidi et al (57) showed that single domestication episodes for both the Mesoamerican and Andean gene pools, with strong bidirectional gene flow between domesticated and wild species, provided the best fit to data on 13 loci.…”
Section: When Where and In How Many Geographic Locations Was A Givenmentioning
confidence: 99%
“…The extraordinary phenotypic range of the common bean (Phaseolus vulgaris) has made it a particularly interesting target for domestication research (57). A range of genetic studies (e.g., ref.…”
Section: When Where and In How Many Geographic Locations Was A Givenmentioning
confidence: 99%
“…Common beans have exceptionally wide genetic variation among four gene pools and many races (Tohme et al 1996;Beebe et al 2001) two of which form the focus of sequencing work performed by Mamidi et al (2011). Reflecting this diversity, the CIAT maintains a primary gene bank with more than 36 000 accessions providing raw material for improving the crop using traditional breeding and molecular marker approaches.…”
Section: The Workhopmentioning
confidence: 99%
“…Mamidi et al (2011) have used multilocus sequence data to test models for domestication of common beans. Their data support a single domestication event in each of the MesoAmerican and Andean gene pools, and provide needed information for more precise association mapping and selection.…”
Section: The Workhopmentioning
confidence: 99%